Blockchain in FinTech: Applications, and Limitations - Durgeswar, Vempalli R; Srinivas, C.C. Kalyan (International Journal of Computer Sciences and Engineering, 2025)
The Internet and digitization have already turned many elements upside down. The financial sector is no exception. Today, a new epoch of financial service, called “FinTech,” has emerged. Blockchain, an innovation by FinTech, has attracted considerable attention. Blockchain is a relatively new technology that has shown a lot of possibilities. It emerged in 2009 as a public ledger of all bitcoin transactions. It became more popular since it can be used as backbone for various applications in finance, media, smart property, smart healthcare, security, governmental services and many more. Motivated by the recent explosion of interest around Blockchains, we examined various blockchain’s applications. This paper discusses about Blockchain characteristics and also presents its limitations. This work even explores the types of fraud and malicious activities that can be prevented by Blockchain technology and identifies attacks to which Blockchain remains vulnerable. Here we also discuss about using Blockchain to Avert Online Attacks.